STRESSFUL SITUATIONS IN THE WORK OF A MULTIPROFILE PEDIATRIC MEDICAL FACILITY'S CALL CENTER - I. M. Spivak; E. G. Biryukova; M. I. Slipka; I. N. Chernomurov (Union of pediatricians of Russia, 2015)
Stressful situations in the work of a pediatric medical facility's call center are associated with patients' violation of social communication norms and aggressive behavior, as well as the operator's professional/maternal conflict. The following psychological resources facilitate better stress resistance of operators: self-confidence, mature and rational attitude, personal activity, inner satisfaction, optimism, emotional breadth and emotional colleague support.